Examining the Factor Structure of the Self-Report of Psychopathy Short-Form Across Four Young Adult Samples. (December 2017) - Dotterer, Hailey L.; Waller, Rebecca; Neumann, Craig S.; Shaw, Daniel S.; Forbes, Erika E.; Hariri, Ahmad R.; Hyde, Luke W.
Psychopathy refers to a range of complex behaviors and personality traits, including callousness and antisocial behavior, typically studied in criminal populations. Recent studies have used self-reports to examine psychopathic traits among noncriminal samples. The goal of the current study was to examine the underlying factor structure of the Self-Report of Psychopathy Scale–Short Form (SRP-SF) across complementary samples and examine the impact of gender on factor structure. We examined the structure of the SRP-SF among 2, 554 young adults from three undergraduate samples and a high-risk young adult sample. Using confirmatory factor analysis, a four-correlated factor model and a four-bifactor model showed good fit to the data. Evidence of weak invariance was found for both models across gender. These findings highlight that the SRP-SF is a useful measure of low-level psychopathic traits in noncriminal samples, although the underlying factor structure may not fully translate across men and women.